Mempelajari Laju Pendinginan Beberapa Jenis Produk Pertanian - Meike Meilan Lisangan (Fakultas Pertanian Universitas Papua, 2009)
The physicochemical change within harvested fruit generally correlated to the oxidative metabolisms, including respiration (Muchtadi, 1992; Pantastico et.al., 1989). The change rate of this process may be anticipated by stored in low temperature (cooling effect). Deterioration process might be occurred as a result of abnormal ripening when the proper storage temperature is not achieved (Muchtadi, 1992). The aim of this experiment was to determine the cooling rate of some agriculture products. Banana fruit, tomato and carrot were wrapped by stretch film packaging and store with thermokopel set up in the center of the fruits. The results showed that the cooling rate of banana was higher than tomato and carrot about 0.1664°C/mins, 186°C/mins, and 0.1287°C/mins, respectively.